非圆齿轮-圆柱齿轮动力学对比仿真研究 - 郑方焱; 李波; 吴又安; 陈定方; 沈小华 (Jixie chuandong)
Due to the complexity of gear tooth profile and the time-varying feature of gear contact ratio,it is difficult to use existing theoretical methods to study its dynamical behavior.Therefore,it is significant to seek for an easy and reliable new way to study its dynamical behavior.By taking apair of non-circular gear transmission of a specific transmission ratio function and a pair of cylindrical gear transmission as a contrast experiment,based on ADAMS,the experimental results with the corresponding theoretically calculated values from the angular velocity,angular acceleration,meshing force as well as other dynamical behaviors are compared.This study provides a new idea not only for the intensive research on the difference between non-circular gear transmission and cylindrical transmission,but also for the application of the modifying achievements of cylindrical gear to the field of non-circular gear transmission.